Rancangan Bangun Sistem informasi akademik padaTaman Kanak-kanak : Academic Information System in Kindergarten - Sampe, Frederica; Rindengan, Yaulie D. Y.; Lumenta, Arie S. M. (Universitas Sam Ratulangi, 2024)
Abstract — Technology facilitates our daily activities, including in the field of education. In this research, the aim is to develop an Academic Information System for a Kindergarten, using TK NAOMI as an example. The system is designed to streamline the exchange of information, such as planned activities for students and reports on their completed activities. All activities are scheduled, making it convenient for parents to be informed about the learning plans and activity reports of their children. The system is developed using the PHP programming language with the Laravel framework, and MySQL is employed as the database for storing data. This web-based application is designed to simplify the exchange of information between teachers and parents regarding the development of the child. It ensures that information about teachers and students is well-organized and structured. The research aims to ease the tasks of teachers and provide parents with convenient access to information about their child's school activities. Keywords: Academic information system; Kindergarten, Abstrak — Teknologi memudahkan kita dalam beraktifitas sehari – hari, bergitu pun dalam dunia pendidikan, teknologi membantu dalam pengelolaan data , dalam penelitian kali ini bertujuan untuk membangun sistem informasi akademik Taman kanak-kanak dalam kasus ini diambil contoh TK NAOMI , dimana sistem yang di bangun memudahkan dalam proses pertukaran informasi misalnya kegiatan – kegiatan yang akan di lakukan oleh peserta didik, serta laporan kegiatan yang telah dilakukan oleh peserta didik , semuanya telah terjadwal sehingga memudahkan orang tua untuk mengetahui rencana pembelajaran serta laporan kegiatan peserta didik sistem ini dibangun dengan bahasa pemograman PHP dengan menggunakan frame work Laravel , serta database MySQL sebagai media penyimpanan data , Aplikasi berbasis Web ini dirancang agar guru dan orang tua di permudah dalam pertukaran informasi perkembangan anak, serta data-data informasi guru dan anak dapat tersimpan dengan baik dan terstruktur Hasil penelitian ini di harapkan dapat mempermudah tugas guru serta mempermudah orang tua untuk mengetahui kegiatan anak di sekolah Kata kunci : Sistem infromasi akademik ; Taman kanak-kanak